2020
DOI: 10.21203/rs.3.rs-80033/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude and practices related to COVID-19 among young Lebanese population

Abstract: Background: As the world faces the most serious and widespread pandemic in recent history, claiming nearly 700,000 lives and infecting close to 17 million individuals, controlling the spread of COVID-19 is still limited to efforts done by the general population implementing rules and restrictions passed by world governments and organizations. Awaiting the development of a cure or a vaccine, the best approach to fighting the spread of this disease is mostly preventative depending largely on individuals’ complia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The level of attitude towards COVID-19 among pregnant mothers was found 62.46%, which is comparable with a study conducted in a low‐resource African setting 60.9% [ 35 ]. However, it is lower than the study conducted among the young Lebanese population 90% [ 36 ]. The discrepancy might be due to differences in study population and study variable measurement.…”
Section: Discussionmentioning
confidence: 65%
“…The level of attitude towards COVID-19 among pregnant mothers was found 62.46%, which is comparable with a study conducted in a low‐resource African setting 60.9% [ 35 ]. However, it is lower than the study conducted among the young Lebanese population 90% [ 36 ]. The discrepancy might be due to differences in study population and study variable measurement.…”
Section: Discussionmentioning
confidence: 65%
“…[28] Another systematic review and meta-analysis of 84 studies from 45 countries or territories, that comprised a total of 215,731 participants, has found that knowledge scores ranged from 72% for low-income countries to 79% for upper-middle-income countries and reported a pooled knowledge score of 75%. [29] On the other hand, similar studies from Malaysia, [30] India, [31] Lebanon, [32] and China [33] have found somewhat lower knowledge levels about COVID-19, but not as low as that observed in a study conducted in Bangladesh, which showed that only 33% of the participants had a good level of knowledge about COVID-19. [34] The fact that during this study's data collection period, Brazil had one of the fastest-growing COVID-19 epidemics in the world, [2] which resulted in it being the country with most cases and deaths in Latin America, [35] and the intense coverage of the pandemic by Brazilian mainstream media, with high-quality content due to the participation of well-known researchers and health professionals, [36] might explain the high level of knowledge found in this study.…”
Section: Discussionmentioning
confidence: 77%
“…[28] Another systematic review and meta-analysis of 84 studies from 45 countries or territories, that comprised a total of 215,731 participants, has found that knowledge scores ranged from 72% for low-income countries to 79% for upper-middle-income countries and reported a pooled knowledge score of 75%. [29] On the other hand, similar studies from Malaysia, [30] India, [31] Lebanon, [32] and China [33] have found somewhat lower knowledge levels about COVID-19, but not as low as that observed in a study conducted in Bangladesh, which showed that only 33% of the participants had a good level of knowledge about COVID-19. [34]…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Daoust (2020) identified the correlates of compliance with preventive measures across 27 countries, with a focus on older adults. In the context of Lebanon, some work has tried to identify correlates of adherence to preventive measures (Domiati et al, 2020), sometimes for some subpopulations (Abou-Abbas et al, 2020; Nasser et al, 2020; Sakr et al, 2021), while other work has looked at the role of specific interventions in affecting or mediating adherence (Melki et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%